2008
DOI: 10.1158/1541-7786.mcr-08-0039
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Frizzled-Related Protein 4 Regulates Two Wnt7a Signaling Pathways and Inhibits Proliferation in Endometrial Cancer Cells

Abstract: In the endometrium, hormonal effects on epithelial cells are often elicited through stromal hormone receptors via unknown paracrine mechanisms. Several lines of evidence support the hypothesis that Wnts participate in stromal-epithelial cell communication. Wnt7a is expressed in the luminal epithelium, whereas the extracellular modulator of Wnt signaling, secreted frizzled-related protein 4 (SFRP4), is localized to the stroma. Studies have reported that SFRP4 expression is significantly decreased in endometrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 44 publications
6
104
0
Order By: Relevance
“…To our knowledge, this is the first evidence that Wnt7a can inhibit canonical Wnt signaling. One possible mechanism for the observed inhibitory effect could be that Wnt7a activates the noncanonical planar cell polarity (PCP) pathway in tissue culture cells (12,40). However, given our developmental genetics studies and the fact that Wnt7a and Wnt5a, which can also activate the PCP pathway (58,61), exerted different effects on Wnt3-induced gene expression, we propose that the inhibitory effect of Wnt7a on canonical Wnt3a signaling in tissue culture cells could be mediated by a poorly understood noncanonical pathway involving Lmx1b (37).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first evidence that Wnt7a can inhibit canonical Wnt signaling. One possible mechanism for the observed inhibitory effect could be that Wnt7a activates the noncanonical planar cell polarity (PCP) pathway in tissue culture cells (12,40). However, given our developmental genetics studies and the fact that Wnt7a and Wnt5a, which can also activate the PCP pathway (58,61), exerted different effects on Wnt3-induced gene expression, we propose that the inhibitory effect of Wnt7a on canonical Wnt3a signaling in tissue culture cells could be mediated by a poorly understood noncanonical pathway involving Lmx1b (37).…”
Section: Discussionmentioning
confidence: 99%
“…40 The ability for sFRP4 to antagonize both the canonical ␤-catenin and noncanonical c-JNK pathways is in accordance with a previous study, which reported that sFRP4 antagonized Wnt7a signaling via both the canonical ␤-catenin and noncanonical c-JNK pathways in endometrial cancer cells. 41 Therefore, sFRP4 exhibits a multilevel effect on ␤-catenin. It directly antagonizes the canonical Wnt/␤-catenin pathway and also the noncanonical Wnt/planar cell polarity pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Both canonical and non-canonical Wnt signalling pathways have been shown to be activated by Wnt7a, and SFRP4 was shown to antagonize Wnt7a mediated signalling and inhibit proliferation of endometrial cancer cells [89]. Wnt7a is expressed in the luminal epithelium, with SFRP4 localised to the stroma and there was an interaction seen between them by immunoprecipitation, which could possibly explain SFRP4 mediated inhibition in Wnt7a signalling activation.…”
Section: Endometrial Cancermentioning
confidence: 98%